An analysis of the patients presenting to a private hospital emergency department in the Ethekweni Metrpolitan area during holiday and non-holiday periods - Dayaram, Mukund Manhur (My University, 2015)
Background: There has always been anecdotal reports that the ED is busier during the holidays and this increase in utilization is due to an increased incidence of trauma. Methods The retrospective data was collected from the Study Hospital’s Database and from the billing records of the doctor practice managing the ED. The data included all patients attending the Study Hospital ED during November 2011 (Non-holiday Period) and between the 10th December 2011 and 8th January 2012 (Holiday Period). Results: It was noted that the age, gender and racial profile of the patients attending the ED during the Holiday and Non-holiday Periods were similar. However there was a 39.9% increase in ED utilization during the Holiday Period. The Holiday Period was also associated with increased utilization by tourists (29.9% vs. 8.2%); with a slightly lower incidence of trauma (23.4% vs. 24.6%); with patients presenting with less urgent Triage Scores; fewer patients arriving at the ED via ambulance (3.2% vs. 7.2%) and a lower admission rate (10% vs. 17.5%). Conclusions: There was a significant increase in the utilization of the Study Hospital ED during the Holiday Period. This increased utilization was due to an increase in visitors to the Umhlanga area during the Holiday Period and was associated with an increased presentation to the ED of low acuity patients probably as a result of a lack of availability of their GP.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Medicine in Emergency Medicine Johannesburg, 2015
Keywords: Emergency Service, Hospital; Retrospective Studies; Health Care Surveys